Nanotechnology and nano-propolis in animal production and health: an overview - Seven, Pinar Tatli; Seven, Ismail; Baykalir, Burcu Gul; Mutlu, Seda Iflazoglu; Salem, Abdelfattah Z. M. (Taylor & Francis Ltd, 2018)
Nanotechnology is the science and technology of small and specific things that are <100 nm in size. Because of the size of nanomaterials, new changes in their chemical and physical structure may occur, and indicate higher reactivity and solubility. Many of nanotechnology applications in food and agricultural production are being developed in research and development settings. Global challenges are related to animal production, including environmental sustainability, human health, disease control, and food security. Nanotechnology holds promise for animal health, veterinary medicine, and some areas of animal production. Nanotechnology has had application in several other sectors, and its application in food and feed science is a recent case. Especially, natural nano antimicrobials obtained from different techniques such as nano-propolis are useful to veterinary medicine in terms of health, performance, and reliable food production. Nano-propolis is a nano-sized (1-100 nm in diameter) propolis particles tied together to make it more effective without changing its properties by changing the size of propolis by different methods. Propolis have many advantages such as anti-inflammatory, antioxidant, anticancer and antifungal activity, etc. The consumption of free form of propolis restricts these benefits due to low bioavailability, low solubility, low absorption, and untargeted release. Different nanoencapsulation technologies are used to obtain nano-propolis. Nano-propolis are more easily absorbed by the body because they have a size smaller. Nano-propolis is also more effective than propolis in terms of antibacterial and antifungal activity. This review focuses on some recent work concerning the uses of nanotechnology in animal health or human health using animal models, and the effectiveness of nanotechnology on natural supplements such as propolis used in animal nutrition and animal health.
Keywords: Nanotechnology; animal production and health; nano antimicrobials; nano-propolis